2007
DOI: 10.2174/138945007779940188
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cathepsin K in Normal Joints and in the Development of Arthritis

Abstract: Cysteine cathepsins are a large family of proteolytic enzymes active at acidic pH as found in lysosomes. Since its discovery in 1990's, cathepsin K has been shown to be a key enzyme in osteoclastic bone resorption through its activity in the resorption lacuna. Although characteristic to osteoclasts, the expression of cathepsin K has also been observed at other sites in skeleton. Several recent observations have demonstrated up-regulation of cathepsin K in osteoarthritic cartilage and inflamed synovial tissue. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(57 citation statements)
references
References 0 publications
0
53
0
4
Order By: Relevance
“…Several studies have also demonstrated the upregulation of this cysteine protease in cartilage and synovium of inflamed joints, and it is believed to play an important role in the destruction of articular cartilage (reviewed in [44]). In the present study, cathepsin K transcription levels were elevated in synovial tissue in response to carrageenan-induced inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also demonstrated the upregulation of this cysteine protease in cartilage and synovium of inflamed joints, and it is believed to play an important role in the destruction of articular cartilage (reviewed in [44]). In the present study, cathepsin K transcription levels were elevated in synovial tissue in response to carrageenan-induced inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that cysteine proteases especially cysteine cathepsins were also involved in the degradation of cartilage matrix [3,4]. Among them, cathepsin K received main attention as it is capable to cleave type I and II collagens as well as aggrecan [5,6]. Elevated gene expression of cathepsin K has been noted in articular cartilage in transgenic mouse for OA, supporting the correlation between cathepsin K and OA [7].…”
Section: Introductionmentioning
confidence: 88%
“…The disease is characterized by a high degree of clinical and pathophysiological heterogeneity. The destruction of cartilage in arthritic conditions is believed to be catalyzed by matrix metalloproteases (MMPs), aggrecanases, and probably cathepsins [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%